2015
DOI: 10.1002/adom.201500319
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Optical Fibers – An Innovative Platform for In‐Fiber Photonic Devices

Abstract: The field of hybrid optical fibers is one of the most active research areas in current fiber optics and has the vision of integrating sophisticated materials inside fibers, which are not traditionally used in fiber optics. Novel in‐fiber devices with unique properties have been developed, opening up new directions for fiber optics in fields of critical interest in modern research, such as biophotonics, environmental science, optoelectronics, metamaterials, remote sensing, medicine, or quantum optics. Here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(35 citation statements)
references
References 193 publications
(274 reference statements)
0
35
0
Order By: Relevance
“…Liquid crystals have properties between those of conventional liquids and those of solid crystals. For instance, a LC 3 For a recent partial review on hybrid fibers based on solid materials, see Alexander Schmidt, Argyros, and Sorin (2016). 4 See, e.g., Kerbage et al (2002), Mach et al (2002), Domachuk, Nguyen, and Eggleton (2004), Kuhlmey, Eggleton, and Wu (2009), Markos, Vlachos, and Kakarantzas (2010, Markos, Antonopoulos, and Kakarantzas (2013), , and Vaiano et al (2016) and early reviews by Kerbage and Eggleton (2004) and Eggleton et al (2005).…”
Section: Liquid Crystal-filled Pcfsmentioning
confidence: 99%
“…Liquid crystals have properties between those of conventional liquids and those of solid crystals. For instance, a LC 3 For a recent partial review on hybrid fibers based on solid materials, see Alexander Schmidt, Argyros, and Sorin (2016). 4 See, e.g., Kerbage et al (2002), Mach et al (2002), Domachuk, Nguyen, and Eggleton (2004), Kuhlmey, Eggleton, and Wu (2009), Markos, Vlachos, and Kakarantzas (2010, Markos, Antonopoulos, and Kakarantzas (2013), , and Vaiano et al (2016) and early reviews by Kerbage and Eggleton (2004) and Eggleton et al (2005).…”
Section: Liquid Crystal-filled Pcfsmentioning
confidence: 99%
“…The basic structure of an integrated thermal flow sensor in a fiber is shown in Figure , which is fabricated using a thermal drawing process that has recently been demonstrated for a variety of sensors and actuators for light, heat, and sound . We take advantage of the exceptional aspect ratios and dimensional control of this processing technique to place an extraordinarily long and thin polymer hot film adjacent to a hollow core that serves as a fluid channel.…”
mentioning
confidence: 99%
“…Materials 2020, 13, x FOR PEER REVIEW 10 of 20 modification [77]; different solid [15,16,[78][79][80][81] and liquid materials [82] were injected into the fiber hollow regions. Among others, one can highlight such well-described approaches for the injection of host materials such as pressure-assisted melt filling ( Figure 12) [79], chemical vapor deposition [83], and direct fiber drawing [77]. Schmidt M. et al reported different hybrid MOFs realized though the selective or complete filling of the fiber air channels by the metal wires or molten glasses.…”
Section: Hybrid Microstructured Optical Fibersmentioning
confidence: 99%